Age and Sex-Specific Relationships between Phthalate Exposures and Obesity in Chinese Children at Puberty - Zhang, Yunhui (Public Library of Science, 2014)
OBJECTIVE: To examine the age and sex-specific associations of urine levels of six mono-phthalates with body size and fat distribution in Chinese children at puberty. MATERIALS AND METHODS: Four hundred and ninety-three school-aged children (247 boys, 246 girls) were recruited. Obesity related anthropometric indices were measured and body fat proportion (BF%) was calculated. Spot urine samples were collected and phthalate monoesters were detected by an API 2000 electrospray triple quadrupole mass spectrometer (ESI-MS/MS). Associations between phthalate exposure and overweight/obesity measures and their trends were examined by multiple linear regression and Logistic regression analyses, respectively. RESULTS: Di-2-ethylhexyl phthalate (DEHP) metabolites and monobutyl phthalate (MBP) were found to be the most detectable chemicals. In 8–10 years (yrs) group, concentrations of MEHP and MBP were significantly higher in girls than those in boys. However, concentrations of all phthalate monoesters, except for MEP and MEHP, in 11–13 yrs boys were significantly higher than those in girls. After adjusting for confounders including puberty onset, urinary concentrations of MBP and sum of low molecular-weight phthalate metabolites (∑LMP) were positively associated with boys' obesity in a concentration-effect manner, while concentrations of MEHP, MEHHP and sum of DEHP metabolites (∑MEHP) were negatively associated with girls' obesity. Associations between phthalate exposure levels and BMI z-score changes were age- and sex-specific in school-age children. CONCLUSION: There are age and sex-specific concentration-effect associations between phthalate exposure and fat distribution in Chinese children. Urinary phthalate levels in 11–13 yrs boys were about 30 percent higher than those in girls, and ∑MEHP levels in younger boys (<10 yrs) were significantly higher than those in elder boys (>10 yrs). Associations were positive for MBP and ∑LMP with both BMI z-score and fat distribution in boys >10 years of age, and negative for ∑MEHP with fat distribution in girls <10 years of age.